Psychosocial Stressors Associated with Depression Among Young Adults in Bandung, West Java, Indonesia. - Niman, Susanti; Parulian, Tina Shinta; Sibarani, Dahlia; Siagian, Ira Octavia; Lee, Ka Yiu (New Voices in Psychology)
The early stage of adulthood is a critical period of interpersonal, educational, and career development, leading to an increased risk of depression. While studies examining psychosocial stressors among depressed young adults have been conducted in developed countries, more efforts are needed to identify the risk factors in developing countries. This study aimed to identify the psychosocial stressors associated with depression among young adults in Bandung, West Java, Indonesia. This cross-sectional study recruited 341 respondents aged 18 – 40 (mean age 21.7). The Beck Depression Inventory-II were used to identify the level of depression, and the psychosocial stressors were self-reported. Bivariate and multivariate analyses assessed the risk factors of depression. Results: A total of 39% of participants had severe depression. The level of depression was higher in participants who were government employee (p<.001), were living with a partner(p<.001), and had experienced being bullied (p<.05). Types ofoccupation was a significant predictor (p<.001) of levels of depression, adjusting for socio-demographic factors and other psychosocial stressors. Special attention needs to be placed on promoting mental health among people who live with a partner, have experience of being bullied and those who work in the government sectors in Indonesia.